2019
DOI: 10.1186/s13643-019-0940-9
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review protocol of stigma among children and adolescents with epilepsy

Abstract: BackgroundEpilepsy is a neurological condition that is highly prevalent among children and adolescents with 80% of the victims living in low- and middle-income countries (LMIC). Epilepsy is associated with high levels of both perceived and enacted stigma, which vary geographically and greatly affects the victims’ quality of life and self-esteem. High rates of stigma are also a significant barrier to accessing medical care. Perceived and enacted epilepsy-related stigma is associated with various sociodemographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 26 publications
(24 reference statements)
0
3
0
Order By: Relevance
“… 16 Self-stigma is a component of the wider social phenomenon of stigma 17 when negative stereotypes and prejudices about a certain condition are widespread in the common thinking of the population. 16 This is widely known for noncommunicable diseases, such as severe mental illness (SMI), 16 substance use disorders (SUD), 18 and epilepsy 19 and communicable diseases such as HIV, 20 and as such, could also occur in people with COVID-19. Research on how stigma had hindered the control of the above-mentioned infectious disease outbreaks might also shed some light on the potential impact of stigma in the battle against the COVID-19 pandemic.…”
Section: Stigma and Infectious Disease Outbreaksmentioning
confidence: 99%
See 1 more Smart Citation
“… 16 Self-stigma is a component of the wider social phenomenon of stigma 17 when negative stereotypes and prejudices about a certain condition are widespread in the common thinking of the population. 16 This is widely known for noncommunicable diseases, such as severe mental illness (SMI), 16 substance use disorders (SUD), 18 and epilepsy 19 and communicable diseases such as HIV, 20 and as such, could also occur in people with COVID-19. Research on how stigma had hindered the control of the above-mentioned infectious disease outbreaks might also shed some light on the potential impact of stigma in the battle against the COVID-19 pandemic.…”
Section: Stigma and Infectious Disease Outbreaksmentioning
confidence: 99%
“…Hospital de Magalhães Lemos, Porto, Portugal. 19 School of Population Health, University of Auckland, Auckland, New Zealand. 20 Unit of Clinical Psychiatry, Dept.…”
mentioning
confidence: 99%
“…Epilepsy is a chronic neurological disorder, affecting more than 70 million people worldwide, with an estimated prevalence of 0.5% to 1%. [ 1 5 ] Of those, patients with epilepsy who fail to respond to antiepileptic drug treatment are defined as having drug-resistant epilepsy (DRE). [ 6 9 ] It has been reported that about 30% patients with epilepsy suffer from DRE.…”
Section: Introductionmentioning
confidence: 99%